2005
DOI: 10.1016/j.jim.2005.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Laser capture microdissection and single-cell RT-PCR without RNA purification

Abstract: Chronic infectious diseases of the central nervous system (CNS) are characterized by intrathecal synthesis of increased amounts of immunoglobulin G (IgG) directed against the agent that causes disease. In other inflammatory CNS diseases such as multiple sclerosis and CNS sarcoid, the targets of the humoral immune response are uncertain. To identify the IgGs expressed by individual CD38+ plasma cells seen in human brain sections, we merged the techniques of laser capture microdissection (LCM) and single-cell RT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…It allows accurate investigation of subcellular or tissue-specific profiles, including disease-associated ones, especially when combined with PCR amplification, gene expression assays [EmmertBuck et al, 1996;Nakazono et al, 2003], proteomic analysis [Xu et al, 2002], enzyme recovery from LCM-transferred tissue [Emmert-Buck et al, 1996], or even profiling at the single-cell level [Kamme et al, 2004;Keays et al, 2005]. The proposed approach of mapping scaffolds to chromosomes using LCM is a fast and cost-efficient way for acquiring chromosomal information for draft genome assemblies, avoiding likely errors of reference-or synteny-based approaches.…”
Section: Discussionmentioning
confidence: 99%
“…It allows accurate investigation of subcellular or tissue-specific profiles, including disease-associated ones, especially when combined with PCR amplification, gene expression assays [EmmertBuck et al, 1996;Nakazono et al, 2003], proteomic analysis [Xu et al, 2002], enzyme recovery from LCM-transferred tissue [Emmert-Buck et al, 1996], or even profiling at the single-cell level [Kamme et al, 2004;Keays et al, 2005]. The proposed approach of mapping scaffolds to chromosomes using LCM is a fast and cost-efficient way for acquiring chromosomal information for draft genome assemblies, avoiding likely errors of reference-or synteny-based approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue preparation and laser capture were performed using a strategy similar to one previously described (7). Tissue specimens were sectioned on a cryostat at ϳ10 m, mounted onto glass slides, fixed in acetone for 30 s, and then placed in PBS.…”
Section: Laser Capture Microdissection Of Single B Cells and B Cell Cmentioning
confidence: 99%
“…RNA was extracted from tissue sections 8-to 15-m thick using the Absolutely RNA Nanoprep Kit (Stratagene) according to the manufacturer's instructions. Alternatively, RNA was extracted directly from single cells and cell clusters present on LCM caps according to a procedure previously described (7). From the total RNA, cDNA was synthesized and human Ig variable region genes were amplified according to the protocol described by Wang and Stollar (8), with minor modifications that included the use of the TOPO TA vector (Invitrogen) for cloning and subsequent sequencing of PCR products.…”
Section: Ig Variable Region Cloningmentioning
confidence: 99%
“…Although procedures for reverse transcription of unpurified total RNA in the cell lysates have recently been published to be applied to LMD samples (Kobayashi et al, 2003;Hoang and Pasloske, 2004) and single-cell RT-PCR (Keays et al, 2005), most papers reported the use of extraction methods that are appropriate for small samples, such as those achieved by LMD (Parlato et al, 2002;Burgemeister et al, 2003;Niyaz et al, 2005;Jin et al, 2001). Home made developed methods for RNA isolation can be used but, since the number of different preparation protocols is unlimited, each user should optimize and follow strictly his own protocol as regard to staining, fixation and extraction of RNA from microdissected tissue samples.…”
Section: Rnamentioning
confidence: 99%